The dynamic relation between fertilization, precipitation and the diffusion of agricultural non-point pollution in Hainan Island - Wang, Shuogen; Zhou, Shudong (Frontiers in Environmental Science, 2024)
With the increasing demand for crops, the excessive application of fertilizers has gradually become a significant factor affecting water quality. Therefore, studying the relationship between agricultural fertilizer runoff and water quality is crucial for the sustainable development of agricultural production. The present study sets up a new dynamic model of nitrogen fertilizer loss, introducing variables such as precipitation, fertilization application during dry and rainy seasons, and their lagged and interaction terms. The paper analyzed the issue of fertilizer runoff under the complex interactions of various factors, including spatial and temporal scales and climatic conditions, and explored the relationship between agricultural activities and water quality changes in the context of sustainable development. Due to Hainan Island’s independent river system, which is free from transboundary pollution, and its low level of industrial pollution, it provides an excellent sample for assessing the impact of agricultural non-point source pollution on water quality. Based on watershed monitoring data from Hainan Island, this study draws the following conclusions: 1. Precipitation exhibits a pronounced seasonal influence on total nitrogen concentration. 2. Nitrogen fertilizer enters into water bodies through precipitation, resulting in a lag effect on total nitrogen concentration. 3. The influence of grain and tropical crops on nitrogen loss is less significant, while cash crops will trigger the nitrogen overloading of rivers in scenarios where they account for a high proportion of the planting structure of the sown area.